Correct diagnostic conclusion in patients with chronic heart failure: a reality or a pipe dream? - V. V. Kalyuzhin; A. T. Teplyakov; I. D. Bespalova; E. V. Kalyuzhina; V. L. Ostanko; N. N. Terentyeva; I. K. Livshits; A. A. Shalovay; O. F. Sibireva; M. A. Solovtsov (Бюллетень сибирской медицины, 2020)
The authors of this article have analyzed the problem of diagnostic conclusion unification in patients with chronic heart failure (CHF). The root of this problematic situation in which practitioners find themselves is that, despite the large number of different regulatory documents, there is no consensus on what is considered correct and what is wrong when formulating a diagnostic conclusion in a patient with CHF. The many-faced syndrome is designated differently: CHF, congestive heart failure, chronic circulatory failure. There are difficulties in determining the stage of CHF in patients receiving optimal drug therapy or in those who are in a state of compensation after a successful surgical correction. When assessing the functional status in a patient with CHF, a distinct subjectivity should be taken into account in determining which limited physical activity is slight or, conversely, marked, as well as what kind of physical exertion is normal for the patient. This subjectivity naturally leads to low reproducibility of the assessment results of the CHF functional class in the same patient by different doctors. CHF should also be classified according to the value of a left ventricular ejection fraction. The diagnosis should also take into account the state characteristics of a diastolic function of the left ventricle (especially in patients with CHF and preserved left ventricular ejection fraction). The authors give examples of diagnostic conclusions, including cases of comorbid pathology.